The examination of circular and elliptical vanes under natural convection of nanofluid in a square chamber subject to radiation effects - Raisi, Afrasiab; Rostami, Sara; Nadooshan, Afshin Ahmadi; Afrand, Masoud (International communications in heat and mass transfer, 2020)
In this paper, natural convection and radiation heat transfer of alumina-water nano-fluid in a square chamber at 45° has been simulated. The right wall of the chamber is cold, and there is a warm vane in the chamber. The vane can change form into horizontal ellipse, vertical ellipse, and circle. The other parts of the walls are insulated. The simulation was performed by using the algebraic control volume method and the SIMPLE algorithm. The effective parameters include the Rayleigh number, the radiation parameter, the nanoparticle volume percentage, and the vane dimensions. The paper focuses on finding the best vane size for maximum heat transfer. The results show that the intensification of the Rayleigh Number and addition of nanoparticles augments heat transfer. As the Rayleigh number enhances by up to 105, the Nusselt number increases up to 3 times. The intensification of nanoparticles concentration up to 4% also increases the Nusselt by 2.5% compared to water. Adding radiation heat transfer to the chamber can significantly increase heat transfer. Increasing the radiation parameter from 0 to 3 has increased the Nusselt number by more than 7 times. The Nusselt number increases with increases in both vane diameters. Nevertheless, it is strongly dependent on the horizontal diameter, and changes in the vertical diameter have little effect on the average Nusselt Number (Nuave).